2011
DOI: 10.1007/s10295-011-0950-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of lipase production by Staphylococcus warneri EX17 using the polydimethylsiloxanes artificial oxygen carriers

Abstract: In this research, the combined effects of polydimethylsiloxane (PDMS) and different conditions of oxygen volumetric mass transfer coefficient (k(L)a) on lipase production by Staphylococcus warneri EX17 were studied and optimized in bioreactor cultures. Raw glycerol from biodiesel synthesis was used as the sole carbon source. Full-factorial central composite design and the response surface methodology were employed for the experimental design and analysis of the results. The optimal polydimethylsiloxane concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The nonlinear relationship of fermentation process variables, namely, inoculum concentration and temperature on lipase yield from Geobacillus thermoleovorans CCR11 has been also found through the RSM approach [19]. Significant and combined effects of polydimethylsiloxane (PDMS) and oxygen volumetric mass transfer coefficient through RSM have been acknowledged by Rech et al [20] for lipase production by Staphylococcus warneri EX17.…”
Section: Resultsmentioning
confidence: 99%
“…The nonlinear relationship of fermentation process variables, namely, inoculum concentration and temperature on lipase yield from Geobacillus thermoleovorans CCR11 has been also found through the RSM approach [19]. Significant and combined effects of polydimethylsiloxane (PDMS) and oxygen volumetric mass transfer coefficient through RSM have been acknowledged by Rech et al [20] for lipase production by Staphylococcus warneri EX17.…”
Section: Resultsmentioning
confidence: 99%
“…The author observed a 3‐fold increase in the oxygen uptake rate of immobilized T. versicolor in polyurethane foam with the addition of 0.5% silicone to cultures. Finally, Rech et al 28 studied the impact of adding non‐emulsified poly‐dimethylsiloxane (PDMS) to S. warneri cultures and reported the positive effects of this chemical concerning the production of lipases, which was around 50% higher when compared with cultivations without PDMS. Moreover, the authors reported a reduction in time to enzyme peak production of one‐half, while enhancing the oxygen transfer rates of cultures.…”
Section: Resultsmentioning
confidence: 99%